2016
DOI: 10.3233/jad-160304
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Crocus sativus L. in Patients with Mild Cognitive Impairment: One Year Single-Blind Randomized, with Parallel Groups, Clinical Trial

Abstract: There is evidence to suggest the efficacy of Crocus (saffron) in the management of cognitive decline. This study examined the efficacy of Crocus in patients with amnesic and multi domain MCI (aMCImd). The participants included 17 patients on Crocus and 18 on a waiting list, who were examined with a short neuropsychological battery, MRI 3T, while some patients were examined via 256-channel electroencephalogram (HD-EEG) at baseline and after 12 months. The results showed that patients on Crocus had improved Mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 22 publications
0
73
0
4
Order By: Relevance
“…1315 Besides, Crocus sativus tested in AD patients showed to mildly enhance the patinets’ cognitive function. 16,17 Crocus sativus contains more than 150 volatile and aroma-yielding compounds along with carotenoids including zeaxanthin, lycopene, and various α - and β -carotenes. 18 However, Crocus sativus ’s golden yellow-orange color is primarily the result of crocins, which are considered as major constituents; whereas the picrocrocin and safranal are responsible for its bitterness and aroma, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1315 Besides, Crocus sativus tested in AD patients showed to mildly enhance the patinets’ cognitive function. 16,17 Crocus sativus contains more than 150 volatile and aroma-yielding compounds along with carotenoids including zeaxanthin, lycopene, and various α - and β -carotenes. 18 However, Crocus sativus ’s golden yellow-orange color is primarily the result of crocins, which are considered as major constituents; whereas the picrocrocin and safranal are responsible for its bitterness and aroma, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…placebo [20]; 12 weeks of 7.5 g/day Choto-san extract [TJ-47] versus no treatment [30]; 52 weeks of Crocus extract versus waitlist [29]). Two other studies [27, 28] reported similar changes in the control condition: both reported increased P300 amplitudes (26 weeks of 5 mg/day donepezil [27, 28] or 1.5 mg/day rivastigmine [28]), and 1 reported reduced P300 latencies (26 weeks of 5 mg/day donepezil) [27].…”
Section: Resultsmentioning
confidence: 99%
“…Incidence of side effects was comparable in the two treatment groups, while vomiting was associated with the donepezil treatment. Furthermore, a randomized single‐blind 12‐month study showed that saffron improved the cognitive decline in 17 participants with amnesia (Tsolaki et al, ). Moreover, saffron proved comparable to memantine in reducing cognitive decline in patients with moderate to severe Alzheimer's disease (Farokhnia et al, ).…”
Section: Potential Therapeutic Applications Of Saffronmentioning
confidence: 99%
“…Despite being multiple mechanistic studies, only a few clinical trials proved that saffron could improve depression symptoms and stimulate cognitive functions in patients suffering from Alzheimer's disease (Broadhead, Chang, Grigg, & McCluskey, ; Farokhnia et al, ; Tsolaki et al, ). Due to its supposed aphrodisiac effects, saffron has also been tested in preclinical and clinical studies regarding male and female sexual disorders, mainly caused by major depression (Hosseinzadeh, Ziaee, & Sadeghi, ).…”
Section: Introductionmentioning
confidence: 99%